Предмет: Алгебра, автор: Dianka981

Помогите пожалуйста решить. Желательно подробное решение

Приложения:

Ответы

Автор ответа: NNNLLL54
0
2^{10x^2-8x-23}+2^{5x^2-4x-12}-3=0\\2cdot (5x^2-4x-12)=10x^2-8x-24\\10x^2-8x-23=(10x^2-8x-24)+1\\2^{t}=2^{5x^2-4x-12}; ; to ; ; 2^{2t+1}+2^{t}-3=0\\2cdot 2^{2t}+2^{t}-3=0\\y=2^{t} textgreater  0; ; to ; ; 2y^2+y-3=0; ,y textgreater  0\\D=1+4cdot 2cdot 3=25; ,; y_1=frac{-1-5}{4}=-frac{3}{2} textless  0; ; nepodxodit\\y_2=1 textgreater  0\\2^{t}=1; ,; 2^{t}=2^0; ; to ; ; t=0

5x^2-4x-12=0\\D/4=4+5cdot 12=64\\x_1=frac{2-8}{5}=-frac{6}{5}; ,; x_2=frac{2+8}{5}=2\\Otvet:; -frac{6}{5}=-1frac{1}{5}=-1,2; ;; ; 2.\\oo
Похожие вопросы